Retinoblastoma in times of war: changing patterns of presentation, treatment, and prognosis in Gaza - Yousef, Yacoub A.; Msallam, Mohammad; Mohammad, Mona; Halalsheh, Hadeel; Khzouz, Jakub; Al-Hussaini, Maysa; Jaradat, Imad; Shawagfeh, Munir; Sultan, Iyad; Mehyar, Mustafa; Al-Nawaiseh, Ibrahim; Mansour, Asem (Frontiers in Oncology, 2026)
BackgroundRetinoblastoma (Rb) is a curable childhood eye cancer when treated early, yet survival remains far lower in developing countries than developed countries. Delayed access to specialized care is a key barrier, and armed conflicts further worsen outcomes. Since October 2023, Gaza has endured a devastating war and complete siege, leading to health system collapse, medicine shortages, and restricted movement. This study examined the impact of war-related delays on presentation, treatment, and outcomes in Gaza’s Rb patients.MethodsWe retrospectively analyzed 12 children (17 eyes) with retinoblastoma treated at King Hussein Cancer Center (2016–2025), grouped into pre-war (2016–Oct 2023; 7 patients, 10 eyes) and during-war (Oct 2023– Oct 2025; 5 patients, 7 eyes) cohorts. Data included presenting signs, lag time, stage, treatment, eye salvage, metastasis, and survival.ResultsMedian lag-time increased from 30 days before the war to 180 days (range 120-270) during the siege. Disease severity was significantly worse: before the war, only 20% of eyes were group E and none had extraocular disease, whereas during the war 57% were group E and 29% presented with extraocular extension(p=0.036). Eye salvage dropped dramatically, from 70% pre-war to 29% during the war(p=0.046). Primary enucleation rose nearly threefold, from 20% before the war to 57% during the siege, and 20% in the war had bilateral enucleation. Critically, while no patient in the pre-war cohort developed metastasis or died, 40% of children during the war developed metastasis and 20% died.ConclusionThe siege during the Gaza war had a devastating impact on outcomes. It substantially increased the risk of death from retinoblastoma; an otherwise highly curable childhood cancer when timely treatment is available. Outcomes were dictated not by medical limitations but by political and humanitarian barriers. Urgent international action is essential to secure humanitarian corridors, safeguard children’s right to timely cancer treatment, and ensure healthcare is protected from the effects of war.